The effectiveness of dry heat treatment (fluidotherapy) in patients with distal radius fracture followed conservatively: a single-blinded, randomized controlled clinical study - Cigdem-Karacay, Basak; Horoz, Levent; Ceylan, Ismail; Alkan, Halil (Assoc Medica Brasileira, 2025)
OBJECTIVE: The effectiveness of fluidotherapy has not been investigated in patients with distal radius fracturedistal radius fracture. AIMS: The aim of this study was to investigate the effectiveness of fluidotherapy added to conventional rehabilitation programs on pain, edema, muscle strength, and functionality in conservatively followed distal radius fracture patients. METHODS: The present randomized controlled, single-blinded study was conducted with 40 distal radius fracture patients who were followed conservatively with a cast. The patients were divided into two groups: the fluidotherapy and conventional rehabilitation groups. In addition to the conventional rehabilitation programs, the patients in the fluidotherapy group received 30 sessions of fluidotherapy for 6 weeks. Rest and activity pain were measured with the Numeric Rating Scale, edema with the Figure 8 method, joint range of motion with goniometry, handgrip strength with a dynamometer, and functionality with the patient-rated wrist evaluation questionnaire. Outcome measures were assessed at baseline, at week 2, and at week 6. RESULTS: Statistically significant changes were found in the intragroup measurements for all parameters in both groups (p<0.05). In the measurements between the groups, there was a statistical difference in the Numeric Rating Scale rest and range of motion flexion values in the conventional rehabilitation group and in the range of motion pronation parameters in the fluidotherapy group (p<0.05). No difference was found between the groups in the other parameters (p>0.05). CONCLUSION: Adding fluidotherapy to distal radius fracture rehabilitation had no effect on activity pain, edema, muscle strength, or functionality. Improvement in resting pain among distal radius fracture patients was less with the addition of fluidotherapy. Fluidotherapy was effective only on wrist pronation.
Keywords: Wristfractures; Hand; Range Of Motion; Physical Therapy Modalities; Edema